TINGKAT PENGETAHUAN PADA KECEMASAN REMAJA TERHADAP COVID-19 DI SMPN 16 KERINCI - Sari, Putri Minas; Nur, Siti Aisyah; Diana Morika, Honesty; Idaman, Meldafia (E-Jurnal Medika Udayana, 2022)
Covid-19 has become a worldwide pandemic disease. In Indonesia, every year the anxiety rate continues to increase, estimated at 20% of the world's population and as many as 47.7% of adolescents feel anxious. The purpose of the study was to determine the relationship between knowledge levels and anxiety levels against covid 19 in adolescents at SMPN 16 Kerinci. This type of research is descriptive-analytic with a cross-sectional design. The research was conducted at SMPN 16 Kerinci on June 22, 2021. The study population was all students of grades VII and VIII at SMPN 16 Kerinci using proportional random sampling techniques. Data collection using questionnaires was analyzed through univariate and bivariate analysis. The results showed that adolescents whose knowledge level was sufficient and moderate had the same value, which was 34% and the level of moderate anxiety and no symptoms had the same value, which was 34%. The results of the Chi-square test found a relationship between the level of knowledge and the level of anxiety about Covid-19 in adolescents at SMPN 16 Kerinci (p-value 0.019 < 0.05). The results of the study concluded that there is a relationship between the level of knowledge and the level of anxiety about Covid-19, it is hoped that the principle of SMPN 16 Kerinci can form a Covid-19 task force team in schools to be more vigilant about Covid-19.